Dapagliflozin in the management of type 2 diabetes mellitus: a real-life experience in Bangladesh (BIRDEM Medical Journal, 2020)
Background: Dapagliflozin, a selective renal sodium-glucose cotransporter-2 inhibitor (SGLT2i), lowers plasma glucose by increasing urinary excretion of glucose. This study evaluated the efficacy and safety of dapagliflozin as add on therapy for a selected group of Bangladeshi type 2 diabetic patients.Methods: This was a 24-week, open-label, prospective, real-life study including type 2 diabetic patients with glycated hemoglobin (HbA1c) 7.0–10% (N =53). Study subjects were selectively assigned to dapagliflozin 5 mg once-daily in the morning along with ongoing oral anti-diabetic drug (OAD). The primary end point was to see the safety (adverse events) and efficacy (reduction of fasting and post-prandial blood glucose, HbA1c) of dapagliflozin.Results: Mean HbA1c changes from baseline to week 24 was – 1.15 ± 0.82 % (P = 0.000) and weight reduction was – 2.49 ± 0.32 kg from base line (P=0.000). Among total study subjects, 6 (11.3 %) had developed urinary tract infection (UTI). There were no major episodes of hypoglycemia or renal function deterioration.Conclusion: Dapagliflozin showed significant reduction of HbA1c as add on therapy. The low incidence of hypoglycemia and UTI make dapagliflozin as an acceptable addition to existing treatment option for type 2 diabetes in Bangladeshi population.Birdem Med J 2021; 11(1): 57-62